PDGF and VEGF Levels in Platelet-Rich Plasma - González, Maczy; Arteaga-Vizcaíno, Melvis; Ruiz, Ana; Briceño, Olga; Quintero, Maribel; Atencio, Ricardo; Estévez, Jesús; Benito, Mariluz; Benito, Marisol; Taborda-Monton, José Luis (The Journal of Dentists, 2013)
PDGF and VEGF are two of the most potent mitogen for connective tissue, its secretion appears to be particularly important when the source is Platelet Rich Plasma (PRP), hence the latter leading role in tissue regeneration. ELISA PDGFBB levels in PRP, Platelet Poor Plasma (PPP) and exudates, were determined in 32 healthy subjects before and 24 hours after ingestion of Aspirin (ASA) and Clopidogrel (CLO). Results: PDGFBB baseline levels were 10.6 ± 1.9 ng / ml (PPP), 12.12 ± 2.5 ng / ml (PRP) and 10.84 ± 1.68 ng / ml (exudate) While after treatment with PDGFBB ASA concentrations were at 8.96 ± 1.4 ng / ml (PPP), 11.36 ± 1.48 ng / ml (PRP), 11.11 ± 1.14 ng / ml (exudate) and the Clopidogrel were 8.53 ± 0.59 ng / ml (PPP), 9.65 ± 1.17 ng / ml (PRP) and 8.51 ± 0.75 ng / ml (exudate) . VEGF basal values were 973.9 ± 590.3 pg / ml (PPP), 1184.2 ± 288.4 pg / ml (PRP), 1069.3 ± 192.3 pg / ml (exudate). After treatment with ASA VEGF values ??were at 1439.5 ± 117.4 pg / ml (PPP), 1802.3 ± 123.9 pg / ml (PRP), 1745.6 ± 171.6 pg / ml (exudate) and the Clopidogrel were 577.8 ± 150.6 pg / ml (PPP), 668.7 ± 100.6 pg / ml (PRP), 624.9 ± 106.7 pg / ml (exudate). Conclusions: It was noted that after administration of antiplatelet drugs PDGFBB and VEGF values decreased statistically significantly, especially for the group of Clopidogrel. The ASA lesser extent appear to affect the concentrations of both factors, which may be attributable to the pharmacological action mechanism between the ASA and Clopidogrel.